2015
DOI: 10.1111/add.12881
|View full text |Cite
|
Sign up to set email alerts
|

Personality, negative affect coping, and drinking alone: a structural equation modeling approach to examine correlates of adolescent solitary drinking

Abstract: Aims This study examined the personality traits of negative emotionality and constraint and the ability to resist drinking during negative affective states as correlates of solitary drinking in adolescence. We hypothesized that higher levels of negative emotionality and lower levels of constraint would predict solitary drinking and that these relationships would be mediated by the ability to resist drinking in response to negative emotions. Design Structural equation modeling was used to fit a path model fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 51 publications
3
56
0
1
Order By: Relevance
“…The current results support the validity of the Criterion B trait model, in so far as they replicate prior work underscoring the importance of trait Disinhibition and Antagonism in the prediction of hazardous alcohol use (e.g., Creswell et al, in press; Few et al, 2013; Kotov et al, 2010; Read, Merrill, Griffin, Bachrach, & Khan, 2014; Ruiz et al, 2008). Notably, these same dimensions are also implicated in various PD diagnoses, including ASPD and BPD (Few et al, 2013; Hopwood et al, 2012; Samuel & Widiger, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…The current results support the validity of the Criterion B trait model, in so far as they replicate prior work underscoring the importance of trait Disinhibition and Antagonism in the prediction of hazardous alcohol use (e.g., Creswell et al, in press; Few et al, 2013; Kotov et al, 2010; Read, Merrill, Griffin, Bachrach, & Khan, 2014; Ruiz et al, 2008). Notably, these same dimensions are also implicated in various PD diagnoses, including ASPD and BPD (Few et al, 2013; Hopwood et al, 2012; Samuel & Widiger, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, individuals who have difficulty abstaining from alcohol or resisting the urge to drink could have the greatest risk of solitary drinking. In partial support of this contention, the relationship between negative affect and solitary drinking was fully mediated by resistance to drink during a negative affective state among an adolescent sample unselected for social anxiety (Creswell et al, 2015). Importantly, Creswell et al found that negative affect was not directly associated with solitary drinking, but rather the inability to refuse a drink during a negative affective state was found to promote problematic drinking behavior.…”
Section: Discussionmentioning
confidence: 90%
“…Fourth, this study did not examine mechanisms that explain how solitary cannabis use may relate to cannabis problems cross-sectionally or longitudinally. Prior studies on adolescent solitary alcohol use have tended to support a self-medication framework, in which adolescents engage in solitary drinking to cope with or relieve negative affect (e.g., Creswell et al, 2014; Creswell et al, in press; Tomlinson and Brown, 2012). There is some evidence that adolescent solitary cannabis users also hold more negative reinforcement expectancies (e.g., beliefs that cannabis use will help them to relax, get away from their problems) than social-only users (Tucker et al, 2006, 2014), and future research should focus on identifying reasons for the emergence of solitary cannabis use among adolescents.…”
Section: Discussionmentioning
confidence: 99%